Kata-kata Serapan Bahasa Belanda pada Bahasa Melayu-Manado (Kajian Morfologi dan Leksikologi) - Sompi, Pingkan Luciawati; Tulung, Golda Juliet; Imbang, Djeinnie (Universitas Sam Ratulangi, 2017)
This research Design entitled â€Loanwords from DutchÂ on Manadonese Malay â€“ a Study of Morphology and Lexicologyâ€is a descriptive analysis. It tends to describe the words in Manadonese Malay, especially adopted words from Dutch. Loanwords or adopted words or borrowing words are words adopted by the speakers of one language from the source language. This is the process of speakers adopting words from a source language into their native language. The words simply come to be used by a speech community when they speakÂ different language, in this case Manadonese Malay. Dutch is the language spoken by Dutch people, especially The Old Dutch who formerly used by Dutch colonialists in Indonesia. Manadonese Malay is spoken in the population of the city of Manado, Bitung, Tomohon, Minahasa districts and surrounding areas. It has similarities with the dialect in Central Sulawesi and Molluca. Most of the words in Manadonese Malay are almost the same in Indonesian, which is the Malay. It is only used for oral communication, there is no standard orthography/writing never ratified.Keywords: Loanwords, Dutch Language and Manado-Malay Language.